Thus burst Hippocrene : studies in the Olympian imagination - Huang, Guobin, (Cambridge Scholars Publishing, 2018)
Thus Burst Hippocrene: Studies in the Olympian Imagination is a collection of nine papers in comparative literature. Discussing the greatest Olympians in world literature, including Homer, Aeschylus, Sophocles, Euripides, Dante, Shakespeare, Milton, Li Bo, Du Fu, and the Bible authors, it is both daring in conception and wide-ranging in scope. Freely drawing on the authors knowledge of Classical Greek, Latin, Italian, French, German, Spanish, English, and Chinese as well as on his conversance with the literatures of these languages, the papers are truly comparative, making discoveries unique to the authors characteristic multi-lingual, multi-cultural approach. In going through the book, the reader will be pleasantly surprised by its originality, by its amazing depth and breadth, and by the new light it sheds on topics that are of interest to scholars and students of comparative literature. Written in lucid language with no pretentious jargon, it will also appeal to the general reader who picks up a book simply for the joy of reading or for horizon-broadening without tears --